2016
DOI: 10.1080/02755947.2016.1204392
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Life History Characteristics of Lake Michigan's Naturalized and Stocked Chinook Salmon

Abstract: Lake Michigan supports popular fisheries for Chinook Salmon Oncorhynchus tshawytscha that have been sustained by stocking since the late 1960s. Natural recruitment of Chinook Salmon in Lake Michigan has increased in the past few decades and currently contributes more than 50% of Chinook Salmon recruits. We hypothesized that selective forces differ for naturalized populations born in the wild and hatchery populations, resulting in divergent life history characteristics with implications for Chinook Salmon popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Our study represents one of few (e.g., Carl 1982;Kerr and Perron 1986;Nack et al 2011;Gerson et al 2016;Kerns et al 2016) to have examined the reproductive ecology of introduced Chinook Salmon in Great Lakes tributaries. As Chinook Salmon fisheries in the Great Lakes become sustained primarily by naturalized populations, an understanding of factors influencing reproductive success and productivity of naturalized populations is becoming increasingly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study represents one of few (e.g., Carl 1982;Kerr and Perron 1986;Nack et al 2011;Gerson et al 2016;Kerns et al 2016) to have examined the reproductive ecology of introduced Chinook Salmon in Great Lakes tributaries. As Chinook Salmon fisheries in the Great Lakes become sustained primarily by naturalized populations, an understanding of factors influencing reproductive success and productivity of naturalized populations is becoming increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies of salmonids in their native range have found differences in spatial habitat use, migration timing, and spawn timing between hatchery and wild fish, even within the same river (e.g., Mackey et al 2001;Quinn et al 2002Quinn et al , 2006Knudsen et al 2006Knudsen et al , 2008Hoffnagle et al 2008;Schroder et al 2008Schroder et al , 2010Dittman et al 2010). In the Great Lakes, Kerns et al (2016) hypothesized that different selective forces between hatchery and naturalized Chinook Salmon populations could lead to evolutionary divergence in life history traits (fecundity, egg size, timing of spawning, and size at maturity). However, information is lacking on the degree of reproductive isolation between hatchery and naturalized fish in hatchery-supplemented populations.…”
mentioning
confidence: 99%
“…The preferred food of Lake Michigan Chinook is the Alewife (Alosa pseudoharengus), a fish related to herring. The relative biomass of Alewives (tons of Alewives per ton of Chinook Salmon) in Lake Michigan varied by a factor of two during the period 1991-2008 [37]. Fig 14 summarizes these data.…”
Section: Comparison With Datamentioning
confidence: 96%
“…Fig 14B plots age at maturity versus weight at maturity for these 18 points; it presents a relatively constant age and an increasing size. We note that the data in Fig 14 broadly represent Lake Michigan Chinook Salmon in that they come from an empirical study [37] of multiple tributaries over many years.…”
Section: Comparison With Datamentioning
confidence: 99%
“…Pacific salmon were introduced to the Great Lakes in the 1960s to control invasive prey fish, rehabilitate predator populations and establish a recreational fishery (Dettmers, Goddard, & Smith, 2012). Since then, salmon have established naturally reproducing populations in many tributaries, while being intensively managed by natural resource agencies (Kerns, Rogers, Bunnell, Claramunt, & Collingsworth, 2016). As a result, managers are concerned about factors such as population instability and contaminant accumulation that might compromise the value of the fishery (Dettmers et al, 2012;Murphy, Bhavasar, & Gandhi, 2012).…”
Section: Introductionmentioning
confidence: 99%